Analisis Rekonstruksi Penyusunan Laporan Keuangan Masjid (Studi Kasus pada Masjid Agung Baiturrahman Banyuwangi) - Arif Hidayatullah; Agung Budi Sulistiyo; Nur Hisamuddin (e-Journal Ekonomi Bisnis dan Akuntansi, 2019)
The mosque is one of the non-profit oriented organizations in the field of religion in carrying out its activities, by managing its resources and resources derived from the community voluntarily and sincerely in accordance with the Statement of Financial Accounting Standards (PSAK) 45 on Nonprofit Organizations, That non-profit organizations should also and are entitled to make financial reports and report to users of financial statements. Mosques must make accurate financial statements and provide information to users of these financial statements ie the donors of the mosque. To be able to make accurate mosque financial statements required the application of accounting. Accounting is an activity undertaken untu produce sautu information system in the form of financial statements. Thus, mosques require the role of accounting as a tool for the process of managing, recording, interpreting, and reporting financial transactions that always guided by PSAK 109 and PSAK 45 set by the Indonesian Institute of Accountants (IAI) which will ultimately produce more transparent financial statements and Accountable. Keywords: Financial Statement of Mosque, Mosque, Nonprofit Organization,, PSAK 109, PSAK 45.